Retrying Galileo, 1633-1992 - Finocchiaro, Maurice A., 1942- (University of California Press, 2005)
A close look at the trial of Galileo in 1633 & the consequences of his condemnation for contending that the Bible is not a scientific authority. In parts of the US and elsewhere, the controversy continues to this day.